2012
DOI: 10.1016/j.psyneuen.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sulfatase-deficient mice exhibit endophenotypes relevant to Attention Deficit Hyperactivity Disorder

Abstract: SummaryAttention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental condition characterised by inattention, impulsivity and hyperactivity; it is frequently co-morbid with anxiety and conduct disorders, sleep perturbation and abnormal consummatory behaviours. Recent studies have implicated the neurosteroid-modulating enzyme steroid sulfatase (STS) as a modulator of ADHD-related endophenotypes. The effects of steroid sulfatase deficiency on homecage activity, feeding/drinking behaviours, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…The 5-CSRTT, a rodent analogue of the human CPT, is a laboratory behavioral task for assessing neurobiological substrates of attention56. Therefore, compatible with our findings, previous data in mice have suggested a link between attention and DHEA(S) levels921222324. The protective effects of DHEA(S) on patients’ neuropsychological function may account for enhancing neuron growth5, regulating GABA A and NMDA activity67, or modulating the complex process of cortical maturation during middle childhood5758.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The 5-CSRTT, a rodent analogue of the human CPT, is a laboratory behavioral task for assessing neurobiological substrates of attention56. Therefore, compatible with our findings, previous data in mice have suggested a link between attention and DHEA(S) levels921222324. The protective effects of DHEA(S) on patients’ neuropsychological function may account for enhancing neuron growth5, regulating GABA A and NMDA activity67, or modulating the complex process of cortical maturation during middle childhood5758.…”
Section: Discussionsupporting
confidence: 87%
“…Several animal studies have revealed that the 39,X(Y)*O mice with deletion of the STS gene exhibit abnormal behaviors and cognitive functions that are relevant to the inattention and hyperactivity that many ADHD patients experience2122. The ADHD-like features seemed to be correlated with the dysregulation of steroid hormone levels and neurotransmitters2324, and improvement may be triggered through administration with DHEA-S25.…”
mentioning
confidence: 99%
“…Results from the 39,X Y* O males were similar to those obtained in females, showing deficits in attention, further implicating Sts (Davies et al , 2009). More recent studies have expanded on those findings, by showing that X Y* O males are hyperactive as compared to XY males and they display increased anxiety in a light-dark box (Trent et al , 2012). However, no direct comparisons have been made between males and females of the Y* cross to determine which other factors, such as gonadal hormones and Y chromosome effects, may also influence attention.…”
Section: Sex Chromosomes and Behaviormentioning
confidence: 98%
“…Humans with STS deficiency are at significantly increased risk of developing ADHD-I and ASD (Kent et al, 2008;Trent et al, 2012).…”
Section: Hormonesmentioning
confidence: 99%